2009
DOI: 10.1016/j.jhazmat.2009.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Selective removal of lanthanides from natural waters, acidic streams and dialysate

Abstract: The increased demand for the lanthanides in commercial products result in increased production of lanthanide containing ores, which increases public exposure to the lanthanides, both from various commercial products and from production wastes/effluents. This work investigates lanthanide (La, Ce, Pr, Nd, Eu, Gd and Lu) binding properties of self-assembled monolayers on mesoporous silica supports (SAMMS™), that were functionalized with diphosphonic acid (DiPhos), acetamide phosphonic acid (AcPhos), propionamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 54 publications
3
71
1
Order By: Relevance
“…Rare earth elements (REEs), including Lanthanide elements as well as yttrium and scandium, are widely used in various high-tech applications, such as high strength permanent magnets, automotive catalytic converters, lasers, electronic devices, and superconductors [1][2][3][4][5][6]. As a member of the rare earth family, neodymium (Nd) gains great attention due to high demand in the Nd-Fe-B magnet industry, especially in high performance electric motors in hybrid electric vehicles and direct-drive wind turbine generators [7].…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth elements (REEs), including Lanthanide elements as well as yttrium and scandium, are widely used in various high-tech applications, such as high strength permanent magnets, automotive catalytic converters, lasers, electronic devices, and superconductors [1][2][3][4][5][6]. As a member of the rare earth family, neodymium (Nd) gains great attention due to high demand in the Nd-Fe-B magnet industry, especially in high performance electric motors in hybrid electric vehicles and direct-drive wind turbine generators [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sportsman et al found that dodecanethiol functionalization of mesoporous Poretics membranes showed effective removal of many actinide species (Cs, Sr, Am and Pu), estimating around 70-80 % removal in acidic (HNO 3 ) solution [156]. Recently, Yantasee et al functionalized mesoporous silicas with diphosphonic acid (DiPhos), acetamide phosphonic acid (AcPhos), propionamide phosphonic acid (Prop-Phos), and 1-hydroxy-2-pyridinone (1,2-HOPO) for the selective removal of a number of lanthanides (La, Ce, Pr, Nd, Eu, Gd, and Lu) from both natural waters and acidic aqueous solution and found that over 95 % of 100 g/L of Gd in dialysate was removed by the Prop-Phos mesoporous silica after 1 min and 99 % in 10 min [157]. These particular functionalized mesoporous materials could also be regenerated with a 0.5 M HCl wash without losing the binding properties.…”
Section: Ion-exchange Materials With Chelating Anchor Groups: Polyphomentioning
confidence: 99%
“…In lanthanide atoms, the configuration of the valence electrons of the outermost shell is the same for all the species while the 4f orbitals are progressively filled with increasing atomic number. 2 Screening of the 4f orbitals leads to the extremely similar physical and chemical properties. [1][2][3][4] The structure of the 2-pyridinol-1-oxide (2-PO) and the predicted lanthanide complex is depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%